PEMANFAATAN TEKNOLOGI E-MAIL DAN BLUETOOTH DALAM APLIKASI BLUE PUSH MAIL - Titin Fatimah; Nurullah Nurullah (Universitas Budi Luhur, 2011)
The Internet has transformed the business information systems. Transformation that makes the system connected only in the internal network, becoming a system which can be accessed by the public. Transformation moving more faster, in line with popularity of mobile devices, such as mobile phones and PDAs. Besides the rapid development of hardware, the development of mobile applications are also increasingly supportive. Mobile applications experience a significant acceleration, when Sun Microsystems released the Java mobile edition. Now Java mobile edition became one of the standard features in mobile devices. These revolutionary developments, triggering proliferation of mobile business solutions. This solution enables mobile elements communicate with back-end systems in every place and time. Java has provided a framework that bridges between the back-end systems with mobile clients. So the choice of Java is one solution that should frame the development of use. Mobile-based applications are expected to provide more convenient facilities in exchanging information. By utilizing e-mail technology and Bluetooth, Blue Push Mail application created to help distribute information better, faster and precise.Keywords : mobile device application, information exchange, E-mail, Bluetooth